Application of Novel Amino-Functionalized NZVI@SiO2 Nanoparticles to Enhance Anaerobic Granular Sludge Removal of 2,4,6-Trichlorophenol - Zeyu Guan; Jinquan Wan; Yongwen Ma; Yan Wang; Yajie Shu (Bioinorganic Chemistry and Applications)
A novel amino-functionalized silica-coated nanoscale zerovalent iron (NZVI@SiO2-NH2) was successfully synthesized by using one-step liquid-phase method with the surface functionalization of nanoscale zerovalent iron (NZVI) to enhance degradation of chlorinated organic contaminants from anaerobic microbial system. NZVI@SiO2-NH2 nanoparticles were synthesized under optimal conditions with the uniform core-shell structure (80–100 nm), high loading of amino functionality (~0.9 wt%), and relatively large specific surface area (126.3 m2/g). The result demonstrated that well-dispersed NZVI@SiO2-NH2 nanoparticle with nFe0-core and amino-functional silicon shell can effectively remove 2,4,6-trichlorophenol (2,4,6-TCP) in the neutral condition, much higher than that of NZVI. Besides, the surface-modified nanoparticles (NZVI@SiO2-NH2) in anaerobic granule sludge system also showed a positive effect to promote anaerobic biodechlorination system. More than 94.6% of 2,4,6-TCP was removed from the combined NZVI@SiO2-NH2-anaerobic granular sludge system during the anaerobic dechlorination processes. Moreover, adding the appropriate concentration of NZVI@SiO2-NH2 in anaerobic granular sludge treatment system can decrease the toxicity of 2,4,6-TCP to anaerobic microorganisms and improved the cumulative amount of methane production and electron transport system activity. The results from this study clearly demonstrated that the NZVI@SiO2-NH2/anaerobic granular sludge system could become an effective and promising technology for the removal of chlorophenols in industrial wastewater.